A preliminary report on the 2015 and 2017 field seasons at the Lernagog-1 site in Armenia - Arimura, Makoto; Petrosyan, Artur; Arakelyan, Dmitri; Nahapetyan, Samvel; Gasparyan, Boris (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
The Eo-Holocene Lernagog-1 site (also known as the Lower or Early Holocene, between 10,300 BP and 7500 BP, approximately equating to the last quarter of the 9th millennium BC to the middle of the 6th millennium BC) is a significant period in the Near East as encompasses the transition from hunting-gathering to agriculture. Early farming villages, also known as Pre-pottery Neolithic communities, also appeared at this time and developed in some areas of the Near East.